Challenges to DNA replication in hypoxic conditions - Ng, Natalie; Purshouse, Karin; Foskolou, Iosifina P.; Olcina, Monica M.; Hammond, Ester M. (The FEBS journal, 2018)
The term hypoxia refers to any condition where insufficient oxygen is available and therefore encompasses a range of actual oxygen concentrations. The regions of tumours adjacent to necrotic areas are at almost anoxic levels and are known to be extremely therapy resistant (radiobiological hypoxia). The biological response to radiobiological hypoxia includes the rapid accumulation of replication stress and subsequent DNA damage response, including both ATR‐ and ATM‐mediated signalling, despite the absence of detectable DNA damage. The causes and consequences of hypoxia‐induced replication stress will be discussed. Ribonucleotide reductase (RNR) is a key enzyme required for the synthesis of nucleotides for subsequent incorporation into DNA. In hypoxic (low oxygen) conditions, the composition of RNR is altered to include a stress specific subunit, RRM2B. RRM2B is adapted to function in hypoxic conditions and therefore continue the synthesis of nucleotides.